How Consumer Attitude Mediates Risk Perception and Trust in Using Food Delivery Application - Madiawati, Putu Nina; Wijaksana, Tri Indra (Department of Management, Faculty of Economics and Business, Brawijaya University, 2023)
This study's objective is to observe the variables influencing decisions to use food delivery applications (FDAs) in West Java, Indonesia. We start with the argument that observing risk and trust factors in online transactions were crucial to determine consumer’s attitude and their online purchase behaviour in the end. By surveying 384 individuals and responses were taken from structured questionnaires, the relationships between variables were analyzed using quantitative methods incorporating structural equation model, partial least square (SEM-PLS). The results showed that online purchase behaviour is influenced by risk perception and trust, but mediating effect can cause different results in indirect effects.